(untitled) - Cundey, Dean; 1952-; Attenborough, Richard; 1945-; Williams, John; Kahn, Michael; 1935-; Goldblum, Jeff; 1932-; Koepp, David; Spielberg, Steven; 1946-; et al. (Universal Studios Home Entertainment, 2011)
An archaeologist is invited to tour a new theme park - inhabited by dinosaurs resurrected with their DNA. A double-crossing employee triggers a shutdown of the fencing systems, which causes a terrifying problem. This version has been digitally remastered for enhanced picture and sound. The first installment of the Jurassic Park movie series.
Keywords: United States; Fiction films; Drama; Dinosaurs; Drama; Amusement parks; Drama; Genetic engineering; Film adaptations; Science fiction films; Thrillers (Motion pictures); Action and adventure films